Analisis Tingkat Pemahaman Akuntansi Pada Mahasiswa Akuntansi - Ardiansyah Ardiansyah; Sari Rusmita; Haryono Haryono (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study examines the level of accounting comprehension among students in the Accounting Study Program at Universitas Tanjungpura from two different cohorts, namely 2022 and 2024. A descriptive quantitative approach was employed, with purposive sampling used to determine the sample. A total of 77 active students participated as respondents, consisting of 45 students from the 2022 cohort and 32 students from the 2024 cohort, all of whom had completed or were currently enrolled in basic accounting courses. The research instrument used was an online questionnaire with a Likert scale, covering three main indicators: understanding of basic accounting concepts, ability to prepare journals, and comprehension of financial statements. Data were analyzed using an independent t-test through SPSS version 26. The results revealed that the average comprehension score of students from the 2022 cohort was 61.80 (SD = 8.24), while the 2024 cohort scored an average of 58.19 (SD = 8.70). The t-value of 1.852 with a p-value of 0.068 indicates that the difference in scores was not statistically significant (p > 0.05). This suggests that the difference in entry year does not significantly affect the overall level of accounting comprehension. Instead, factors such as high learning motivation, the effectiveness of teaching methods, and students’ active participation during the learning process are presumed to have a greater impact. Therefore, these findings emphasize the importance of designing learning strategies that are more contextual, interactive, and aligned with the characteristics of today’s students.